2001
DOI: 10.1107/s0907444901016249
|View full text |Cite
|
Sign up to set email alerts
|

Purification, crystallization and preliminary X-ray diffraction of a complex between IL-10 and soluble IL-10R1

Abstract: A complex between interleukin-10 and the extracellular domain of its high-affinity receptor (sIL-10R1) has been crystallized from polyethylene glycol solutions. Crystals suitable for diffraction analysis required the modification of the NXS/T glycosylation sites on sIL-10R1 by site-directed mutagenesis and inclusion of the detergent cyclohexyl-methyl-beta-D-maltopyranoside in the crystallization experiments. The crystals belong to space group P3(2)12 or its enantimorph P3(1)12, with unit-cell parameters a = b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…sIL-10R1Q6 was expressed and purified as described (25). cmvIL-10 (Townes strain) was secreted into the culture media from Drosophila S2 cells (Invitrogen) and purified by affinity chromatography with sIL-10R1 beads.…”
Section: Methodsmentioning
confidence: 99%
“…sIL-10R1Q6 was expressed and purified as described (25). cmvIL-10 (Townes strain) was secreted into the culture media from Drosophila S2 cells (Invitrogen) and purified by affinity chromatography with sIL-10R1 beads.…”
Section: Methodsmentioning
confidence: 99%
“…T213C was expressed in Drosophila S2 cells and purified using an hIL-10 affinity column (25). The receptor was biotinylated with polyethelene oxide-maleimide-activated biotin (Pierce) as described previously (26).…”
Section: Expression Purification and Biotinylation Of Il-10r1 And Imentioning
confidence: 99%
“…Unfortunately, IL-10R2 is a low-affinity receptor [9,48], and it is difficult, if not impossible, to obtain a stable ternary complex capable to crystallize. However, the binary intermediate complexes of both hIL-10 and CMVIL-10 with soluble receptor sIL-10R1 are quite stable and both were crystallized [49]. It was also shown that in solution IL-10 and sIL-10R1 form a complex consisting of two IL-10 dimers and four molecules of sIL-10R1 [50,51]; therefore, the question of the exact stoichiometry of the signaling ternary complex is also open.…”
Section: Stoichiometry Of Ternary and Intermediate/binary Complexesmentioning
confidence: 99%
“…Crystals of a complex of hIL-10 [49] and CMVIL-10 with non-glycosylated mutant of the extracellular domain of IL-10R1 were obtained and both crystal structures were solved [25,52] at resolution 2.9 Å and 2.7 Å, respectively. An asymmetric part of the crystal unit cell of the hIL-10 complex is composed of one domain of hIL-10 and one molecule of sIL-10R1.…”
Section: Stoichiometry Of Ternary and Intermediate/binary Complexesmentioning
confidence: 99%